Improving the Quality of Basic Education: (1) The Issues (2) A Survey of Commonwealth Experience - Commonwealth Secretariat (Commonwealth Secretariat, 1991)
The first paper in this volume is the Commonwealth Secretariat’s issues paper, which served as a background document for the 11th Conference of Commonwealth Education Ministers. The second paper is an overview document that summarizes the country papers, providing selected highlights from the material treated in the individual country papers.
Keywords: Basic education; Commonwealth